Instrument Design to Measure the Critical Thinking Skill of Students that Participate in Chemistry National Science Olympiad - Nugroho, Imam Husnan; Susilaningsih, Endang; Wijayati, Nanik (Journal of Innovative Science Education, 2019)
Critical thinking definition is reasonably and reflectively thinking focused on what to believe or do. In today settings, the ability to think critically is very important, due to the increasing amount of information that must be processed before deciding something. National Science Olympiad is one of the vessels to increase this important skill in our students. Unfortunately, the OSN questions were not designed for measuring this skill. The aim of this research was to design an instrument that measure the critical thinking skill of the OSN participants. This was an R & D type of research, that was done following Four-D method, consists of define, design, development, and dissemination steps. The criteria for a good instrument are validity, reliability, discrimination power, and difficulty level must be sufficient. The result of the research shows that the instrument is valid (89,9% response from experts); reliable (KR-20 is 0,830); with sufficient average of discrimination power (DP is 0,378); and difficulty level (TK is 0,613).